Managing Medium-Term Fiscal Challenges - World Bank (Washington, DC, 2014)
Mexico needs a comprehensive fiscal reform to alleviate the looming medium-term pressures on its budget. This policy note contributes to the debate on Mexico's looming fiscal challenges. The country's fiscal framework, centered on the 2006 budget and fiscal responsibility law, and prudent fiscal risk management has helped maintain short-term budget stability and a fairly stable public debt path, even in times of economic volatility. However, Mexico faces serious longer term fiscal challenges that are not always recognized, measured, and addressed in policy debates, which tend to focus on approving the annual budget. And though Mexico has adopted several policies to mitigate oil-price volatility on the budget, oil production has fallen substantially over the past few years, drawing renewed attention to the longer term challenge of replacing part of the oil-related public revenue base with other, more permanent sources of revenue. Further, spending pressures associated with increasing aging-related spending, public investment, and social spending needs call for a discussion of the fiscal implications of additional impending outlays. Mexico's falling oil revenue and rising public spending needs over the medium term require increased tax revenue and more efficient and better targeted public spending. Looking more closely at this medium- and long-term revenue and spending trends and publishing a medium-term budget outlook would allow for long-term budget planning.